2021
DOI: 10.3389/fpsyg.2021.713353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Information System Quality on Continuance Intention Toward Cloud Financial Information System

Abstract: Cloud financial accounting informatization is a product of the combination of accounting work and information technology, a current demand for financial information management in the new era, and a necessary means for enterprises to enhance their core competitiveness. Therefore, this study is based on DeLone and McLean's information system success model, and through theoretical interpretation and derivation, we integrate satisfaction and trust in relationship quality to measure the impact of users' intention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 114 publications
2
11
0
2
Order By: Relevance
“…The findings revealed that SQ is the top predictor, of, AIS, use from the other predictors examined and that maybe related to the varying importance level of the ISs success models constructs based on the attributes of the organization ( Almaiah et al, 2022k ; Heo & Han., 2003 ). Evidently, centralized computing in firms stress more on system quality rather than information quality as reported by Petter and McLean (2009) and this is aligned with other studies as well (e.g., Almaiah et al, 2022l ; Hsu et al, 2015 ; Lin et al, 2006 ; Li & Wang, 2021 ). In these studies, system quality covers flexibility of the system and its reliability, urging the user towards system use, which ultimately leads to their satisfaction.…”
Section: Discussionsupporting
confidence: 85%
“…The findings revealed that SQ is the top predictor, of, AIS, use from the other predictors examined and that maybe related to the varying importance level of the ISs success models constructs based on the attributes of the organization ( Almaiah et al, 2022k ; Heo & Han., 2003 ). Evidently, centralized computing in firms stress more on system quality rather than information quality as reported by Petter and McLean (2009) and this is aligned with other studies as well (e.g., Almaiah et al, 2022l ; Hsu et al, 2015 ; Lin et al, 2006 ; Li & Wang, 2021 ). In these studies, system quality covers flexibility of the system and its reliability, urging the user towards system use, which ultimately leads to their satisfaction.…”
Section: Discussionsupporting
confidence: 85%
“…DMISS2003 model argues that InfQ, as outputs of an IS, is one of the main constructs interpreting satisfaction and usage (DeLone and McLean, 2003). Indeed, numerous studies leveraged the DMISS2003 model and examined the effect of InfQ on use and user satisfaction in various contexts such as hospital IS (Ojo, 2017), project management IS (Lee and Yu, 2012), enterprise resource planning systems (Ouiddad et al , 2021), cloud financial information system (Li and Wang, 2021), internet banking (Al-Hattami et al , 2021a), education management IS (Martins et al , 2019) and E-government services (Owusu et al , 2022). Most of these studies revealed a positive impact of InfQ on usage and user satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[12] argued that system quality relates to the technical features of a system, such as its usability and accessibility. [13] reported that system quality, information quality, and service quality as dimensions influencing user satisfaction and successful usage of the information system, as subsequent indicators illustrating the success of the information system from a cause-and-effect perspective. [33] defined information quality as the accuracy of information delivered to customers without errors and the ability to clarify what is meant.…”
Section: System Qualitymentioning
confidence: 99%